Learning to Pray. (December 2014) - Beck, Joan
Abstract Joan Beck writes a personal account of how her life of prayer has developed since graduating from seminary in 1978. She tells how, through prayer, the Holy Spirit enlivened the presence of Christ in her as she learned to listen more than talk and weathered dry spells of no response. She hopes that by including reports and resources from her own journey, readers will be moved to reflect upon and share what they have learned through prayer.